Materialistic objections against cartesian dualism (Archives of Clinical Psychiatry, 2013)
I discuss five basic objections materialists often raise to Cartesian Mind-Body Dualism: (1). It is not empirically testable or confirmable; (2). It is in principle testable and confirmable, but unconfirmed; (3). It is testable and confirmable, but has been shown false; (4). It is unnecessary to explain anything; and (5). It cannot serve to explain anything. I will show how unsatisfactory all these objections are. If I am right in what I argue the reductionist posture of contemporary materialism against the existence of Cartesian Immaterial Substances as causal agents in explaining human behavior, is demonstrably more dogma than anything else. Moreover, the promise of reductive materialism to explain human personality, consciousness, and behavior is unlikely ever to be fulfilled.